Detection of microplastics in commercial bottled mineral water - Olong, Nurannisah (2025)
Microplastic ranging in size from 1 μm to 5 mm are contaminants in bottled mineral water, raised significant health concerns. This study aims to detect the presence of microplastics in commercially bottled mineral water. A total of 18 local bottled mineral water were used as sample in this study. Six samples were analysed using temperature test, in which the three samples were exposed to room temperature (25°C ± 2°C) and another three were exposed to peak temperature (60°C ± 2°C). Another 12 samples were undergoing shaking test. In shaking test, the samples were exposed to two different temperatures (room and peak temperature) and speeds (30 and 60 RPM). Each three samples were exposed to room temperature at 30 RPM, peak temperature at 30 RPM, room temperature 60 RPM, and peak temperature at 60 RPM. After temperature and shaking test were completed, the samples underwent reusability test where they underwent their respective tests for three repeated uses. To observe the presence of microplastic particles, the samples were filtered through nylon-66 membrane filter 0.45-micron pore size. The microplastics were observed under a stereomicroscope to determine the quantity, shape, and colour of microplastic particles. The results highlighted that samples that were exposed to high thermal stress (60°C ± 2°C) and mechanical stress (30 and 60 RPM) leached more microplastics. In terms of the microplastic shape, fragment, fibre, filament, and film were presented in the samples and predominantly by fragment microplastics. The colour of microplastics detected in the samples were transparent, green, and dark grey with transparent colour predominantly. Repeated use of bottles did not lead to an increase in microplastic leaching. Instead, the number of microplastic particles detected varied inconsistently in each bottle. To conclude, this study may raise awareness among consumers to take necessary precautions to minimise the potential microplastics contamination in their bottled mineral water.